2015
DOI: 10.1016/j.juro.2014.08.123
|View full text |Cite
|
Sign up to set email alerts
|

Bullying has a Potential Role in Pediatric Lower Urinary Tract Symptoms

Abstract: To our knowledge our study is the first to show that 1) bullying is significantly associated with pediatric lower urinary tract symptoms and 2) physical forms of bullying accompany worsened symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
2
9
0
4
Order By: Relevance
“…More children in the bullying group reported urinary symptoms. [ 13 ] The higher anxiety level in the abuse victims was suggested to play a role in the development of urinary symptoms. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…More children in the bullying group reported urinary symptoms. [ 13 ] The higher anxiety level in the abuse victims was suggested to play a role in the development of urinary symptoms. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…This principle was perhaps best exemplified by Zhao 29 and Ching 30 et al, who found significant associations between bullying and the prevalence of pediatric LUT symptoms. Improved bathroom conditions may discourage students from holding urine, which can have downstream positive health implications.…”
Section: Discussionmentioning
confidence: 96%
“…17 Additionally, Arlen et al 18 presented 25 patients with phantom urinary incontinence and concomitant LUTSs and constipation, and 70% of the kids had a diagnosis of OCD. And in a comparison of 38 kids with LUTSs versus 38 kids without LUTSs, Zhao et al 19 found an anxiety level score higher in the group with LUTSs (3.68 versus 0.97; p < 0.001).…”
Section: Discussionmentioning
confidence: 97%